The relationship between e-commerce and customer satisfaction at government sector in Perbadanan Kemajuan Negeri Kedah, Alor Setar, Kedah / Muhammad Farid Ikhwan Senu - Senu, Muhammad Farid Ikhwan (2014)
With the development of Internet, e-commerce is developing rapidly in Malaysia a a new way for online business transaction. Therefore, it is important for this research paper to identify the determinants of consumer satisfaction towards e-commerce for among government servant in Perbadanan Kemajuan Negeri Kedah (PKNK), Alor Setar, Kedah. /\ total of 110 e-commerce users had participated in this research. The findings revealed that website design, payment method, information quality, security and privacy are positively related to customer satisfaction towards e-commerce among government servant in Perbadanan Kemajuan Negeri Kedah (PKNK), Alor Setar, Kedah. Data are gathered through survey among the government servant in Perbadanan Kemajuan Negeri Kedah (PKNK), Alor Setar, Kedah which has experience in e-commerce.